AKSESIBILITAS INFORMASI KEPEMILUAN BAGI PENYANDANG DISABILITAS DI BAWASLU KOTA SURABAYA - pinayungan sitoresmi (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2026)
Accessibility of electoral information is a crucial element in supporting the realization of inclusive democracy, particularly for persons with disabilities who still experience various limitations in obtaining public information. Equal access to election information enables the public to understand their political rights and actively participate in the democratic process. This study aims to analyze the accessibility of election information. The study used a qualitative method with a descriptive approach throuh observation, documentation, and literature review related to public communication and inclusive democracy. The results show that the dissemination of election information has been carried out through digital publications, institutional documentation, and public communication activities. However, information accessibility still does not fully accommodate the needs of persons with disabilities due to limited disability-friendly media, a lack of alternative information formats, and suboptiomal inclusive communication strategies. From a social inclusion perspective, limited access to information can lead to social  exclusion and low political participation of vulberable groups. Therefore, it is necessary to strengthen inclusive public communication and develop accessible information media to support equal political participation and inclusive democracy.